Changes in strategic foods and farmers' terms of trade that are causally related - Suri, Oktaviani Tribara; Olviana, Tomycho; Chamdra, Santhy; Nendissa, Doppy Roy; Mahendra, Bayu (Anjoro: International Journal of Agriculture and Business, 2024)
This study seeks to analyze the price fluctuations of strategic food items, specifically rice and cayenne pepper, in NTT Province, and to examine the correlation between these price changes and the farmer exchange rate in the region. Fluctuations in the prices of food goods in substantial volumes can significantly impact the inflation rate. The study that was conducted made use of secondary data, which was collected from the NTT Provincial Central Statistics Agency. These data were in the form of a time series. The coefficient of variation and multiple linear regression analysis were two of the analytical methodologies that were used. The price of cayenne pepper undergoes substantial fluctuations over time. The price of rice and NTP exhibit a significant positive correlation, indicating that an increase in rice prices is associated with an increase in NTP, consistent with the positive coefficient observed in the regression equation. This research suggests that the government should address fluctuations in rice and cayenne pepper prices by enhancing production and effectively managing supply and demand, thereby improving income and welfare.